The problem of (verb) the thing causes civil liability in Islamic jurisprudence and French jurisprudence - Muhammad, Abdul Bast Jassm (Journal of Legal and Political Studies, 2015)
The expression (action) raises a problem that pictures in the extent of the flexibility of the (thing) with a private subjectivity that allows to it (the action) in other words. Are the (things) hare a private subjectivity and independent movement, and then it hare a special action? Or they are without private life, thus they are without a activity? and is it possible to relate the damage to (the activity of the thing) not to the (Thing) itself? and is that the laws of the responsibility on the activity of things differ according to the difference of the nature of the (Thing) if it was (moving) or (static)? and the disparity of it's role in achieving the damage. If it was (negative) or (positive)? and what role does the palpation and the real connect between the (Thing) and the affected in accusing the responsibility? and what is the status of both Islamic jurisprudence and the legal systems from the responsibility on (The activity of things) and what are the aspects of agreement and difference between them about this responsibility? and with the status of the Arabic laws keep pace with the developments of this subject? Or it is in need to be revision.
Keywords: independent movement; Islamic jurisprudence; responsibility; legal systems